'Living outside the house': how families raising young children in new, private high-rise developments experience their local environment. Issue Volume 13:Issues 3(2020) (2nd July 2020) - Andrews, Fiona J.; Warner, Elyse
ABSTRACT: Families are increasingly choosing to raise children in the growing number of private, high-rise apartment complexes developed in Australian capital cities. However, most of these developments have been designed for the childless and there are concerns as to how supportive these settings are for young children. This paper explores parents' experiences of the environment surrounding their high-rise dwellings in an inner-city municipality of Melbourne, Australia using the participatory method, Photovoice. Ten parents photographed elements of their dwellings and environments that had positive or negative impacts on raising young children. Findings indicate that environments surrounding parents' high-rise dwellings were used on a daily basis, often due to limited space within apartment complexes. However, aspects of this environment were challenging, requiring mutual accommodation between families and their immediate settings. This has implications for policy to ensure the neighbourhoods surrounding high-rise developments in inner-city areas are more child friendly.